Tolerance of maize to Atrazine and Terbuthylazine applied post-emergence - Reinhardt, Carl Frederick (Charlie) (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Weed Science))--University of Pretoria, 2006.